PRIMARY AORTOCAVAL FISTULA IN RUPTURED ABDOMINAL AORTIC ANEURYSM — INSTITUTIONAL EXPERIENCE AND LITERATURE REVIEW - Ribeiro, Tiago (2021)
Introduction: Aortocaval Fistula is a rare clinical entity associated with Abdominal Aortic Aneurysm in less than 1% of cases. Main clinical features include acute heart failure, lower extremety edema, acute kidney injury and acute liver failure. Open surgical repair is associated with high mortality rates (16–66%)(1). On the other hand, endovascular treatment could represent a less morbid and equally efective treatment option. The authors aim to describe clinical presentation, surgical options and post-operative results of the treatment of abdominal aortic aneurysms associated with aortocaval fistula, comparing their results to literature. Material and Methods: A retrospective review in a tertiary care center was designed. All patients treated for aortocaval fistula associated with AAA between January of 2014 and May of 2020 were included. Patient data were obtained by consulting the clinical record. Demographic, clinical, surgery and post-operative results and complications were obtained. Results: During this period, four patients submitted to emergent surgery were identified. All patients were male with a mean age of 70 (±8) years and with tobacco use history (n=4). On admission, most frequent symptoms we're lumbar pain (n=4) and hipotension/tachycardia (n=4). Other frequent signs or symptoms we're abdominal pulsatile mass (n=3) and acute kidney injury with hematuria (n=2). In two patients, CT angiography revealed rAAA with retroperitoneal hematoma without aortocaval fistula, which was only diagnosed intraoperatively. Two patients were submitted to aorto-bi-iliac interposition graft and one to aorto-bi-femoral bypass, all with endoaneurysmal suture of the fistula. One patient was submitted to aorto-bi-iliac EVAR with a Gore Excluder C3® endoprosthesis. Most common post-operative complications were AKI (n=3), respiratory failure (n=2) and acute liver failure (n=2). The aorto-bi-iliac EVAR patient did not present any 30 day post-operative complication and was discharged at the 7th post-operative day. There was 1 secondary intervention within the first 30 days: left hemicolectomy for ischemic colitis. After 30 days we observed one reintervention: implantation of right iliac branch device due to an iliac aneurysm Two patients died in the early postoperative period (2nd and 3rd days). The remaining patients have a follow-up of 29 and 66 months. Conclusions: ACF can occur with or without AAA with retroperitoneal hematoma. In the presence of retroperitoneal hematoma, the ACF could not be evident in CT angiography and only detected intraoperatively. Considering our experience and what is described in literature, we should have a high index of suspicion for this possible complication of rAAA in the presence of acute venous congestion with acute onset of organ failure (AKI, acute cardiac or liver failure), even if CT angiography only reveals retroperitoneal hematoma. Conventional surgery with endoaneurysmal suture of the fistula and interposition graft was the preferred technique, but if endovascular exclusion is feasible, it could be effective and associated with less morbimortality. In endovascular treatment, failure to close aortocaval communication does not appear to result in higher long-term morbidity and monitoring seems plausible in the presence of favorable evolution of the aneurysmal sac and in the absence of symptoms.